Risks and coping strategies in the floodplain economic belt amid drought–flood challenges and climate change - Dong, He; An, Xianjuan; Zeng, Xueting; Li, Tienan; Teng, Yun; Zhang, Xinyu; Li, Shupan (Frontiers in Environmental Science, 2024)
In this study, a coupla risks combination and coping strategies have been developed for confronting conflicts between population-economy development and water resources management (PEWM) due to population-industrial transformation into a floodplain of economic belt under climate change. A location-entropy based PVRA model coupla-risk analysis (LPCR) can be introduced into PEWM to reflect the adverse effects of population-industry transformation on a special function area (e.g., floodplain) of economic belt, where coupla risk map has been addressed. Meanwhile, an adaptive scenario analysis based stochastic-fuzzy method (ASSF) can be joined to deal with multiple uncertainties and their interactions due to subjective and artificial factors.The proposed LPCR and ASSF can be integrated into a risk based stochastic-fuzzy scenario method framework (RSFS) to apply for a practical PEWM case study of Yongding river floodplain in the context of coordinative development of Beijing-Tianjin-Hebei economic belt, China. The results can be presented as follows: (a) Accelerated the population-industry transformation (PIT) into floodplain due to can require more water resources, where each additional unit can promote regional GDP 0.019 unit, increasing water demand 0.046 units. It can strengthen various risks such as water shortage, soil loss and flood control in a floodplain of economic belt. (b) CFW can drop water demand and shortage ratio (would be 0% at highest) for irrigation in the long run, but which would reduce direct economic income of irrigation in the short run. (c) backward irrigative scheme and low water utilization efficiency require a more cleaner production mode, which could reduce water shortages 77.23  10^3 m 3 at highest. (d) the combined policy (S12) can reduce coupla risks (including risk of water shortage, soil loss and flood) than other individual policies (S2, S4, S6 and S8). The findings can assist local decision makers to gain insights into adjusting of interegional strategies not only for remitting populationresource stress in core cities, but also for improving the resilience against drought and flood in a floodplain area, which is conducive the special function of floodplain to support an integrated sustainable development of economic belt.